Histone deacetylase HDAC2 regulates microRNA‐125a expression in neuroblastoma - Denghui Liu; Xianglian Tang; Zhao Huang; Jiabing Wen; Yuxiang Zhou (Brain and Behavior, 2022)
Abstract Background Neuroblastoma (NB) is an infrequent childhood malignancy of the peripheral sympathetic nervous system and is accountable for about 10% of pediatric tumors. microRNA (miR)‐125a has been implicated to serve as a tumor suppressor in various cancers. Herein, we set out to ascertain whether miR‐125a exerts antitumor effects in NB. Methods Downregulated miRNAs were identified by miRNA microarray analysis of NB tissues and paracancerous tissues. The expression of miR‐125a in NB tissues and cells was detected by reverse transcription‐quantitative (RT‐q) PCR, followed by prognostic analysis. Gene Ontology (GO) enrichment analysis was performed on target genes of differentially expressed miRNAs. Cell proliferation, apoptosis, and differentiation were detected by cell counting kit‐8 (CCK‐8), Hoechst staining, immunofluorescence, and western blot. NB cells were injected into nude mice to detect tumorigenic, apoptotic, and differentiation activities in vivo. Dual‐luciferase assay and chromatin immunoprecipitation (ChIP) were carried out to verify the binding relationship between miR‐125a and PHOX2B or histone deacetylases 2 (HDAC2), respectively. Finally, rescue experiments were conducted. Results miR‐125a was downregulated in NB tissues and cells, which was associated with poor prognosis. miR‐125a reduced NB cell proliferation and augmented apoptosis and differentiation. NB cells with miR‐125a overexpression decreased cell tumorigenesis and increased apoptosis and differentiation in xenograft tumor tissues. miR‐125a targeted PHOX2B, which was highly expressed in NB tissues and cells. HDAC2, highly expressed in NB tissues and cells, repressed miR‐125a transcription through histone deacetylation. Overexpression of HDAC2 or PHOX2B rescued the effects of miR‐125a on NB cell proliferation, apoptosis, and differentiation. Conclusion HDAC2 inhibited miR‐125a transcription through deacetylation, and miR‐125a suppressed NB development through binding to PHOX2B.